Concomitant Pulmonary and Biliary Manifestations of Ulcerative Colitis: A Case Report - Pritee Shrestha; Philip Shara; Babajide Adio (Clinical Case Reports)
ABSTRACT Ulcerative colitis can present with extra‐intestinal manifestations, including interstitial lung disease and primary sclerosing cholangitis. When pulmonary symptoms precede gastrointestinal, diagnosis can be challenging. Consideration of Ulcerative colitis in patients with unexplained lung and hepatic pathology is crucial, as a failure of timely intervention can lead to multiorgan complications.